Treatment of a traumatic carotid–cavernous fistula by the sole use of a flow diverting stent. (30th June 2011) - Nadarajah, Mahendran; Power, Mark; Barry, Bryan; Wenderoth, Jason
Abstract : Direct caroticocavernous fistula (CCF) has traditionally been treated by detachable balloon placement within the affected cavernous sinus. We describe a case of a direct CCF treated solely with flow-diverting stents. These novel devices may offer a simpler and potentially safer vessel-sparing option in this rare condition.